2014
DOI: 10.1002/j.2161-0045.2014.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Socioeconomic Status and Proactive Personality on Career Decision Self‐Efficacy

Abstract: This study investigated the relationship of family socioeconomic status and proactive personality to career decision self‐efficacy in a sample of 336 Taiwanese college students. The results of the partial least squares path modeling analysis showed that both socioeconomic status and proactive personality were positively associated with career decision self‐efficacy. These findings support person input variables as being predictive of career decision self‐efficacy and provide career counselors with insight into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 52 publications
8
74
1
5
Order By: Relevance
“…They are relatively unconstrained by environmental factors and are more likely to seek out better solutions to improve their performance in comparison to passive ones. These positive characteristics of proactive personality are expected to trigger a greater sense of self-confidence and selfefficacy, and eventually lead to better outcomes (Hsieh and Huang 2014;Parker and Collins 2010). Many empirical studies also support this hypothesis.…”
Section: Self-efficacy As Mediatormentioning
confidence: 65%
See 1 more Smart Citation
“…They are relatively unconstrained by environmental factors and are more likely to seek out better solutions to improve their performance in comparison to passive ones. These positive characteristics of proactive personality are expected to trigger a greater sense of self-confidence and selfefficacy, and eventually lead to better outcomes (Hsieh and Huang 2014;Parker and Collins 2010). Many empirical studies also support this hypothesis.…”
Section: Self-efficacy As Mediatormentioning
confidence: 65%
“…Recently, according to the studies of proactive personality (Bateman and Crant 1993;Crant 2000;Parker and Collins 2010) and Job Demands-Resources Model (JD-R, Demerouti et al 2001), researchers reported that proactive people are likely to experience high self-efficacy and also engage more frequently in task behaviors (Bergeron et al 2014;Fay and Frese 2001;Hsieh and Huang 2014). Moreover, self-efficacy and work engagement are found to be two critical variables to predict individual's job satisfaction (Judge and Bono 2001;Weiss et al 1999).…”
Section: Introductionmentioning
confidence: 94%
“…Personality traits such as extroversion, openness to experience, agreeableness, and conscientiousness can facilitate the growth of self‐efficacy by helping individuals engage in active planning or goal‐setting (Bullock‐Yowell et al, 2011; Jin, Watkins, & Yuen, 2009). Similarly, proactive personality traits (i.e., a tendency to take action to influence environments) have been positively associated with career self‐efficacy in a sample of Taiwanese college students (Hsieh & Huang, 2014). These findings support the idea that personality traits that help individuals seek out new information and ideas are likely to promote competence in exploring career options and making choices.…”
Section: Career Decision Self‐efficacymentioning
confidence: 99%
“…Proactive personality, referring to "a relatively stable tendency to effect environmental change that differentiates people based on the extent to which they take action to influence their environments" [18] (p. 103), was shown to provide extra explanations for job satisfaction in addition to the Big Five traits [19]. The positive link between proactive personality and CDSE has also been empirically tested [11,20,21]. However, the intervening mechanism underlying this relationship is not clear yet.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a degree of inconsistency between theoretical reasoning and empirical results, which indicates that there is no significant link between family socioeconomic status and vocational self-efficacy [26,27]. Despite this, recent research shows that family socioeconomic status has a positive impact on CDSE [20]. After reviewing 47 relevant studies, Flores and colleagues [28] advocate for further research to discover the moderating effect of family socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%